34. An unusual case of familiar conduction block neuropathy. Issue 4 (April 2016) - Ceccanti, M.; Cambieri, C.; Onesti, E.; Frasca, V.; Tartaglia, G.; Inghilleri, M.
Abstract : Tangier disease is a rare autosomal recessive disorder, resulting from mutations in the ATP binding cassette transporter (ABCA1) gene. The deficiency of ABCA1 protein impairs high-density lipoprotein (HDL) synthesis and cholesterol esters trafficking. A 57 year-old female presenting with intrinsic hands muscles hypotrophy and distal paresthesias was visited in our laboratory in July 2014. The neurological examination showed weakness in orbicularis oculi and oris and in hypotrophic muscles. Moreover, a C3-D12 suspended sensory loss for pain was observed. Similar findings were observed in the two sisters and the brother. ENG–EMG examination detected a reduction in SAP amplitude registered from ulnar and median nerves, bilaterally. cMAPs from the same nerves showed a conduction block neuropathy. Screening laboratory exams were requested. Extremely low levels of total cholesterol (58 mg/dl) and triglycerides (96 mg/dl) were detected. Particularly, HDL levels were almost undetectable (1 mg/dl). We hypothesized a Tangier disease. Patient underwent to abdominal ultrasound detecting a liver echostructure more compact than usual. Cervical dorsal MRI excluded syringomyelic cavities. Reduction in global systolic function and corneal opacity were also observed. Muscle biopsy was normal. Finally, genetic analysis confirmed mutation in ABCA1 in the whole family.